(untitled) (Research, Society and Development, 2021)
Objective: To identify the profile of perpetrators of violence against women in the municipality of Marabá, Pará. Methods: This is a cross-sectional, quantitative and documental retrospective study, carried out from the records of assistance to women victims of violence of the ParáPaz Foundation in the years 2019 (216 records) and 2020 (271 records); analyzed by descriptive statistics and Chi-square test. Results: They were mostly male, in the age range of 30-39 years, with greater representation of spouses and ex-spouses. Conclusion: Violence against women is a problem about which it is necessary to understand its authors. In this sense, based on the data found, it was observed the vulnerability of women from the violence suffered until its notification. The reality evidenced here can instigate new studies to better dimension the phenomenon in the region and provide prevention strategies to this problem, through the implementation of educational actions with the authors of such crimes.